Proses Berpikir Kreatif Siswa SMA dalam Menyelesaikan Masalah Kontekstual Materi Barisan Aritmetika - Syifa’uliyah Syifa'uliyah; Tatag Yuli Eko Siswono; Rini Setianingsih (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Contextual problems are non-routine problems that are related to real or daily life in the form of story questions, so that students are able to apply various contextual problems in learning mathematics. In solving contextual problems, it will be different from one student to another, this is because the creative thinking of each student is not the same. Creative thinking is the process of coming up with many ideas/possible answers of a problem, which has aspects of fluency, originality, and flexibility to generate the ideas. While the stages of creative thinking are: 1) synthesizing ideas, 2) building ideas, 3) planning ideas, and 4) implementing ideas. This research is a descriptive study with a qualitative approach that aims to describe the creative thinking of high school students in solving contextual problems in class X based on the level of creative thinking (creative and creative enough). The subjects in this study were 2 (two) students based on the level of creative thinking. Data collection was done in written form (Creative Thinking Test) and interview. Based on the results of research on creative thinking of high school students in solving contextual problems, information was obtained that: a) students with a creative level of thinking (creative) carry out steps in determining concepts, ideas sourced from everyday experience, generating different ideas from each problem with various patterns, determine and develop strategies to implement ideas based on the information received, but there are a few obstacles in implementing the final problem, but already have a strong concept, even though it is not shown how big the prize is through the stages of synthesizing ideas, building ideas, planning ideas, and implement ideas. b) students with a level of creative thinking (sufficient) carry out steps to recall arithmetic sequence formulas, based on the information obtained in the problem, generate different ideas/patterns based on the knowledge received by students during learning, determine and organize the ideas used, but not thorough in answering the questions, but the ideas given are correct and appropriate and not answering the final problem through the stages of synthesizing ideas, building ideas, planning ideas, and implementing ideas. The implication of this research in mathematics education and learning is to find out the steps for students' creative thinking, knowledge and strategies in solving contextual problems